A Brief Analysis of The Influence of Chinese Culture Ceramic on Rococo Art of The West - Temmy Temmy (Bina Nusantara University, 2014)
Chinese culture elements accepted for the first time by the Western countries was ceramic and silk. China's silk was found in ancient Greece during the Roman era and since then China has become the “Country of Silk”. Chinese ceramics came to the West a bit later. It was during the Song Dynasty that Western countries started accepting Chinese ceramics, and soon after that Chinese Ceramics had became a new surprise to the Western Countries and had China known as the “Country of Porcelain”. Porcelain as a cultural element is considered not only as material but also as a spirit. When the Europeans came to know the porcelain material, they had gradually been influenced by its spiritual content. Delicateness of ceramic slowly became a widely accepted aesthetic style, added with other factors that shaped the formation of the Rococo style that became very popular in Europe. This article used desk study to analyze and summarize the following three aspects: first, the impact of Chinese ceramic art on Western Rococo art, second, the art appreciation of Rococo art and third, to elaborate the influence of Chinese Ceramic and aesthetic in Western Countries.